Virtual Reality as Pedagogical Tool to Enhance Experiential Learning: A Systematic Literature Review - Muhammad Mujtaba Asad (Hindawi Limited, 2021)
Since half of the century, technology has dominated the modern era. The rapid advancement of technology has reached generating artificial intelligence and artificial realities. So, virtual reality is an emerging technology and is applicable in education as well. Virtual reality is a computer-generated simulation, where people can interact within an artificial environment. Moreover, in an educational setting, such an environment provides students with a chance to get experiential learning. This paper has a systematic literature review on emerging technologies, such as virtual reality as a pedagogical tool for enhancing students’ experiential learning. This review aims to explore and understand the effect of virtual reality on students’ experiential learning by reviewing twenty-six selected articles. The selected studies have followed various methodologies and are from different contexts. This review study aims to present a systematic literature review for understanding and exploring the effect of virtual reality as a pedagogical tool for enhancing students’ experiential learning. Nine themes were identified, which are (a) virtual reality as pedagogical tool, (b) virtual reality as emerging educational technology tool, (c) virtual reality as digital transformation, (d) virtual reality as teaching-learning model, (e) virtual reality as architectural pedagogy, (f) virtual reality for communication skills, (g) virtual reality for reading and writing skills, (h) virtual reality for social learning, and (i) virtual reality for experiential learning. Thus, it is found that virtual reality is used as a pedagogical tool for various subject areas for encouraging involvement. It is helpful in medical, engineering, language, and social learning, as it provides a chance to get first-hand experience of the environment. Also, it helps learners to engage in a presented virtual environment and experience the sense of presence in it and enhances students’ experiential learning. Therefore, this review found virtual reality as an essential pedagogical tool for strengthening students’ experiential learning.